Leading service-learning in management education: a framework - Pedro Mota Veiga; António Mendes Ferreira; Célia Ribeiro; Clotilde Passos; Maria José Correia; Paulo Ribeiro; Vitor Figueiredo; Luísa Mota Ribeiro; Carmo Themudo (Gestão e Desenvolvimento)
The adoption of Service-Learning in higher education institutions has emerged as one of the contemporary teaching and learning methodologies. In these contexts, cooperation processes implemented between institutions of higher education and non-profit organizations turn out to be mutually beneficial. Despite the high volume of research on the adoption of Service-Learning, research is scarce on the role of Service-Learning in management courses. Thus, this study aims to conduct a systematic literature review to reflect on approaches to the implementation of Service-Learning in management courses. The process of systematic literature consisted of a review of protocol development, identification of inclusion and exclusion criteria for relevant publications, data extraction, and synthesis. Data were collected from the Web of Science and Scopus databases. The search resulted in 89 articles, with publication dates between 1996 and 2022. Based on the findings of the systematic literature review, we developed a conceptual framework that relates to the existing research on Service-Learning in management courses. We evaluated the applicability of the conceptual model by analyzing the implementation of four projects with the Service-Learning methodology in subjects of the Degree in Management, taught at Universidade Católica Portuguesa – Viseu. The research concludes with the definition of strategies for the implementation of Service-Learning in management education.